A Comparative Analysis of Communal Iftar Practices in Campus and Community Mosques: A Living Fiqh Perspective from Sukoharjo, Indonesia - Della Rahmayani; Azzahra Sindhi Latifa; Qodim Ma'shum (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study examines the practice of communal iftar (iftar jama‘i) across two contrasting institutional settings, namely campus mosques and community mosques in Sukoharjo Regency, Indonesia. It aims to analyze how iftar activities are organized, how patterns of congregational behavior differ, and how these practices can be interpreted within the framework of fiqh al-‘ibādah. Using a qualitative descriptive-comparative approach, data were collected through participatory observation and in-depth interviews with mosque administrators, Ramadan committees, and congregants. The findings indicate that institutional structure plays a significant role in shaping religious practices. Campus mosques tend to implement highly structured and regulated systems, characterized by formal committees, standardized food distribution, and controlled participation mechanisms. In contrast, community mosques exhibit more flexible, participatory, and socially embedded practices, relying on voluntary contributions and collective engagement. Despite these differences, both contexts remain consistent with the normative principles of fiqh al-‘ibādah, particularly in encouraging timely iftar and promoting social charity. These findings demonstrate that religious practices are not static but are dynamically negotiated within specific social contexts. This study reinforces and extends the concept of living fiqh by showing how normative Islamic teachings are continuously interpreted in everyday religious life. It also provides practical implications for mosque management in designing religious activities that balance normative compliance with social inclusivity, thereby offering a more integrated and context-sensitive understanding of contemporary Muslim religious practices during Ramadan.